Assessment of imidacloprid toxicity on reproductive organ system of adult male rats - Bal, R; Türk, G; Tuzcu, M; Yılmaz, Ö; Kuloğlu, T; Gündoğdu, R; Gür, S; Ağca, A; Ulaş, M; Çambay, Z; Tuzcu, Z; Naziroğlu, M; et al. (My University, 2012)
In the current study it was aimed to investigate the toxicity of low doses of imidacloprid (IMI) on the reproductive organ systems of adult male rats. The treatment groups received 0.5 (IMI-0.5), 2 (IMI-2) or 8 mg IMI/kg body weight by oral gavage (IMI-8) for three months. The deterioration in sperm motility in IMI-8 group and epidydimal sperm concentration in IMI-2 and IMI-8 groups and abnormality in sperm morphology in IMI-8 were significant. The levels of testosterone (T) and GSH decreased significantly in group IMI-8 compared to the control group. Upon treatment with IMI, apoptotic index increased significantly only in germ cells of the seminiferous tubules of IMI-8 group when compared to control. Fragmentation was striking in the seminal DNA from the IMI-8 group, but it was much less obvious in the IMI-2 one. IMI exposure resulted in elevation of all fatty acids analyzed, but the increases were significant only in stearic, oleic, linoleic and arachidonic acids. The ratios of 20:4/20:3 and 20:4/18:2 were decreased and 16:1n-9/16:0 ratio was increased. In conclusion, the present animal experiments revealed that the treatment with IMI at NOAEL dose-levels caused deterioration in sperm parameters, decreased T level, increased apoptosis of germ cells, seminal DNA fragmentation, the depletion of antioxidants and change in disturbance of fatty acid composition. All these changes indicate the suppression of testicular function.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Imidacloprid neonicotinoids apoptosis testis sperm characteristics fatty acid composition